Impacto del acceso al agua sobre el cepillado dental en niños menores de 12 años de edad en el Perú, 2017 - Inga Ureta, Yurfa Magaly (2020)
Background: Access to water services is one of the elements that influence the hygiene patterns of the population. Objective: Determine the association between access to water and daily tooth brushing in children under 12 years of age in Peru, 2017. Methods and Materials: Cross-sectional, observational, descriptive and retrospective study. The database of the National Survey on Demography and Family Health (ENDES) 2017 was used. The sample consisted of 19039 records of children under 12 years of age. The response variable was daily tooth brushing, while the predictor was access to water. Covariates such as: access to oral hygiene information, age, sex, Natural Region and Place of Residence were included. A multivariate regression analysis was used to find the association between access to water and daily tooth brushing. Results: From the multivariate analysis between access to water and tooth brushing, the children who obtained water from the tap, public well, tank truck had a PR of 0.94 (95% CI 0.89-0.99; p = 0.012) and the children who obtained water from surface had a PR of 1.04 (95% CI 1.00-1.07; p = 0.052). Conclusion: No association was found between access to water and daily tooth brushing in children under 12 years of age in Peru, 2017.